Analysis of the eight parameter variation of the resonant tunneling diode (RTD) in the rapid thermal annealing process with resistance compensation effect - Zhao, Fan; Wang, Yidian; Guo, Weilian; Cong, Jia; Tee, Clarence Augustine Teck Huo; Song, Le; Zheng, Yelong (American Institute of Physics, 2020)
The rapid thermal annealing process is a key technology to control the parameters of the resonant tunneling diode (RTD) and to achieve high performance for the device. In this paper, the rapid thermal annealing process on the planar RTD has been investigated experimentally. In the experiment, the annealing sample chips of different annealed times have been recorded from the annealing equipment and their I-V characteristics have been measured accordingly. From the I-V characteristics, the negative resistance and the series resistance of the RTD can be obtained. Thus, the relationship between these parameters and annealing time can be established. Finally, by analyzing the concept of the resistance compensation effect, this study explains fully and in detail the dependency of the RTD parameter variation on the annealing time. VP and Vi are significantly reduced, greatly lowering RS, which in return also reduces the heat loss of the circuit and the power consumption of the RTD digital circuits as well as the RTD terahertz oscillator. As VV decreases, negative resistance RN is increased, and thus, the output power of the RTD terahertz oscillator is increased. These results are very useful in the study of RTD devices and fabrication technology. © 2020 Author(s).